FREQUENCY TUNABLE THz-GENERATION IN PERIODICALLY POLED LITHIUM NIOBATE CRYSTAL - Abgaryan, G.K. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2014)
A simple method for the generation of quasi-monochromatic tunable terahertz (THz) pulses via optical rectification of femtosecond laser pulses in periodically poled lithium niobate (PPLN) crystal was proposed. It is shown that when the incidence angle on the crystal of the optical beam changes in the range of –50° to +50°, the central frequency of the generated THz-radiation varies from 0.77 to 0.93 THz and the direction of THz-radiation changes in the range of –10° to +10°. Thus, an appropriate choice of parameters PPLN and the angle of incidence of the laser beam is possible to obtain quasi-monochromatic THz-radiation tunable over a sufficiently wide frequency range.